Time and outcome framing in intertemporal tradeoffs - Scholten, Marc (2013)
A robust anomaly in intertemporal choice is the delay–speedup asymmetry: Receipts are discounted more, and payments are discounted less, when delayed than when expedited over the same interval. We developed 2 versions of the tradeoff model (Scholten & Read, 2010) to address such situations, in which an outcome is expected at a given time but then its timing is changed. The outcome framing model generalizes the approach taken by the hyperbolic discounting model (Loewenstein & Prelec, 1992): Not obtaining a positive outcome when expected is a worse than expected state, to which people are over-responsive, or hypersensitive, and not incurring a negative outcome when expected is a better than expected state, to which people are under-responsive, or hyposensitive. The time framing model takes a new approach: Delaying a positive outcome or speeding up a negative one involves a loss of time to which people are hypersensitive, and speeding up a positive outcome or delaying a negative one involves a gain of time to which people are hyposensitive. We compare the models on their quantitative predictions of indifference data from matching and preference data from choice. The time framing model systematically outperforms the outcome framing model.